Exploring the capacity of endophytic fungi isolated from medicinal plants for fermentation and phenolics biotransformation of rose oil distillation wastewater. Issue 1 (1st January 2019) - Rusanova, Mila; Rusanov, Krasimir; Butterweck, Veronika; Atanassov, Ivan
Abstract: A total of 139 endophytic fungal isolates derived from 20 medicinal and aromatic plants were tested for their capacity to ferment rose oil distillation wastewater (RODW). Internal transcribed spacer sequence-based phylogenetic analysis affiliated the collected isolates to seven genera and nine different species, of which Alternaria alternata was the most widely represented. The fungal fermentation of RODW was evaluated through analysis of the sugar and phenolics content and phenolics composition. After cultivation in a small volume of RODW, the performed cluster analysis grouped the isolates in four distinct clusters according to their capacity to ferment RODW sugars and phenolics. Further larger volume shake-flask cultivation of a selected subset of fungi with a pronounced RODW fermentation capacity, outlined three groups of isolates with a distinct pattern and dynamics of sugars and phenolics fermentation. High-performance liquid chromatography analysis of RODW phenolics extracts following the fermentation by the selected fungal isolates showed two main types of changes in phenolics composition: (1) changes in the relative abundance of part of the RODW phenolic compounds, mainly due to utilization of sugar residues from the RODW phenolic glycosides and (2) biosynthesis of new phenolic compounds, most of which are specific to the endophytic fungal isolates used for RODW fermentation. The overall results of the study clearly demonstrate that endophytic fungal isolates represent a rich and untapped source for efficient fermentation of RODW and other agro-industrial phenolics-rich wastewaters and highlight their capacity for directional changes and modification of RODW phenolics composition towards further wastewater phenolics valorization.